Interior pointwise C2, α regularity for fully nonlinear elliptic equations. (February 2023) - Wu, Duan; Niu, Pengcheng
Abstract: In this note, we prove the interior C 2, α regularity for viscosity solutions of fully nonlinear uniformly elliptic equations with the ellipticity constants close to each other enough. In particular, the regularity for Isaacs equations can be derived. The main idea is the compactness technique.